Topotactic reduction of YBaCo2O5 and LaBaCo2O5: square-planar Co(I) in an extended oxide. - Seddon, J; Suard, E; Hayward, M (2010)
The low-temperature reduction of YBaCo(2)O(5) and LaBaCo(2)O(5) with NaH to form YBaCo(2)O(4.5) and YBaCo(2)O(4.25), respectively, demonstrates that the structures of anion-deficient materials formed by such topotactic reductions can be directed by the ordering and identity of the A-site cations. YBaCo(2)O(4.5) adopts a structure consisting of a corner-shared network of square-based pyramidal CoO(5) and distorted tetrahedral CoO(4) units. The structure of LaBaCoO(4.25) is more complex, consisting of an array of square-based pyramidal CoO(5), distorted tetrahedral CoO(4), and square planar CoO(4) units. Magnetic susceptibility and variable-temperature neutron diffraction data reveal that YBaCo(2)O(4.5) adopts a G-type antiferromagnetically ordered structure below T(N) approximately 280 K. LaBaCo(2)O(4.25) also adopts antiferromagnetic order (T(N) approximately 325 K) with ordered moments consistent with the presence of square-planar, low-spin, s = 0, Co(I) centers. A detailed analysis reveals that the different anion vacancy ordered structures adopted by the two REBaCo(2)O(5-x) phases are directed by the relative sizes and ordering of the La(3+) and Y(3+) cations. This suggests that ordered arrangements of A-cations can be used to direct the anion vacancy order in topotactically reduced phases, allowing the preparation of novel metal-oxygen networks containing unusual transition metal coordination environments.